Trauma Communications Center Coordinated Severity-Based Stroke Triage: Protocol of a Hybrid Type 1 Effectiveness-Implementation Study - Gropen, Toby I.; Ivankova, Nataliya V.; Beasley, Mark; Hess, Erik P.; Mittman, Brian; Gazi, Melissa; Minor, Michael; Crawford, William; Floyd, Alice B.; Varner, Gary L.; Lyerly, Michael J.; Shoemaker, Camella C.; et al. (Frontiers in Neurology, 2021)
Background: Mechanical thrombectomy (MT) can improve the outcomes of patients with large vessel occlusion (LVO), but a minority of patients with LVO are treated and there are disparities in timely access to MT. In part, this is because in most regions, including Alabama, the emergency medical service (EMS) transports all patients with suspected stroke, regardless of severity, to the nearest stroke center. Consequently, patients with LVO may experience delayed arrival at stroke centers with MT capability and worse outcomes. Alabama's trauma communications center (TCC) coordinates EMS transport of trauma patients by trauma severity and regional hospital capability. Our aims are to develop a severity-based stroke triage (SBST) care model based on Alabama's trauma system, compare the effectiveness of this care pathway to current stroke triage in Alabama for improving broad, equitable, and timely access to MT, and explore stakeholder perceptions of the intervention's feasibility, appropriateness, and acceptability. Methods: This is a hybrid type 1 effectiveness-implementation study with a multi-phase mixed methods sequential design and an embedded observational stepped wedge cluster trial. We will extend TCC guided stroke severity assessment to all EMS regions in Alabama; conduct stakeholder interviews and focus groups to aid in development of region and hospital specific prehospital and inter-facility stroke triage plans for patients with suspected LVO; implement a phased rollout of TCC Coordinated SBST across Alabama's six EMS regions; and conduct stakeholder surveys and interviews to assess context-specific perceptions of the intervention. The primary outcome is the change in proportion of prehospital stroke system patients with suspected LVO who are treated with MT before and after implementation of TCC Coordinated SBST. Secondary outcomes include change in broad public health impact before and after implementation and stakeholder perceptions of the intervention's feasibility, appropriateness, and acceptability using a mixed methods approach. With 1200 to 1300 total observations over 36 months, we have 80% power to detect a 15% improvement in the primary endpoint. Discussion: This project, if successful, can demonstrate how the trauma system infrastructure can serve as the basis for a more integrated and effective system of emergency stroke care.